2013
DOI: 10.7314/apjcp.2013.14.7.4127
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-16 Inhibits Bladder Cancer Proliferation by Targeting Cyclin D1

Abstract: MicroRNA-16 (miR-16) has been demonstrated to regulate proliferation and apoptosis in many types of cancers, but its biological function in bladder cancer remains unknown. Here, we found expression of miR-16 to be downregulated in bladder cancer in comparison with the adjacent normal tissues. Enforced expression of miR-16 was able to inhibit cell proliferation in TCHu-1 cells, in line with results for miR-16 antisense oligonucleotides (antisense miR-16). At the molecular level, our results further revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…29,31 Two other recent reports demonstrated that miR-15/16 directly target critical cell cycle regulator Cyclin D1 in bladder cancer and osteosarcoma. 32,33 Another study showed that miR-15/16 expression is downregulated in malignant pleural mesothelioma (MPM). 34 Administration of synthetic mimics to restore miR-15/16 expression led to growth inhibition in MPM cell lines and in xenograft-bearing nude mice; administration of miR-15/16 mimics led to consistent inhibition of MPM tumor growth.…”
Section: Mir-15/16 At 13q14 Gene Discoverymentioning
confidence: 99%
“…29,31 Two other recent reports demonstrated that miR-15/16 directly target critical cell cycle regulator Cyclin D1 in bladder cancer and osteosarcoma. 32,33 Another study showed that miR-15/16 expression is downregulated in malignant pleural mesothelioma (MPM). 34 Administration of synthetic mimics to restore miR-15/16 expression led to growth inhibition in MPM cell lines and in xenograft-bearing nude mice; administration of miR-15/16 mimics led to consistent inhibition of MPM tumor growth.…”
Section: Mir-15/16 At 13q14 Gene Discoverymentioning
confidence: 99%
“…It is well accepted that each miRNA can regulate the expression of many target mRNAs (Jiang et al, 2013;Ling et al, 2013). Several direct targets of miR-9 such as cyclin D1, Ets1 (Zheng et al, 2013), and CXCR4 (Lu et al, 2013) have currently been identified.…”
Section: Discussionmentioning
confidence: 99%
“…MTT assay showed that matrine suppressed the viability of human lung cancer line A549 in dose-and time-dependent manners after cells were treated with matrine at 0.25-4.0 mg/ml for 24, 48, 72 h, respectively. Cell cycle plays a critical role in regulating cell proliferation, growth as well as cell division (Wang et al, 2012;Hernandez-Hernandez et al, 2013;Jiang et al, 2013) . The cell cycle analysis showed that at duration matrine can induce cell cycle arrest at G0/G1 phase and simultaneously decreasing the G2/M phase.…”
Section: Discussionmentioning
confidence: 99%